Graph model for optimal OVSF code placement strategies. (23rd May 2012) - Ouyang, Wen; Yu, Chang Wu; Liu, Meng–Ti; Chang, Yu–Wei
The code utilisation of OVSF–CDMA systems are significantly impacted by the code placement and replacement schemes which have been studied by many researchers as independent problems. We formally define the placement optimality and present a novel graph model, CIDP, which is proved to be NP–complete for general graphs where the CIDP graphs reduced from the OVSF code placement problem are trivial perfect graphs. A unified algorithm UCMS–1, provided to firstly address both OVSF code placement and replacement jointly, achieves placement optimality in linear time complexity. It shows that OVSF code placement optimality problem is in P.